Experimental investigation on underwater drag reduction using partial cavitation - 王宝 汪家道 陈大融 孙娜 王涛 (Chinese physics B, 2017)
For underwater drag reduction, one promising idea is to form a continuous gas or discrete bubbly layer at the submerged surface. Owing to the lower viscosity of gas than of water, this could considerably reduce underwater drag by achieving slippage at the liquid–gas interface. This paper presents an experimental investigation on underwater drag reduction using partial cavitation. Dense hydrophobic micro-grooved structures sustain gas in the valleys, which can be considered as defects that weaken the strength of the water body. Therefore, partial cavities are easily formed at lower flow speeds, and the dense cavities connect to form a lubricating gas layer at the solid–liquid interface. The results indicate that the proposed method achieves drag reduction without any additional energy or gas-providing devices, which should stimulate the development of underwater vehicles.